Clinical researchIs there any correlation between TNF-related apoptosis-inducing ligand (TRAIL) genetic variants and breast cancer? - Yildiz, Yemliha; YaylIm-Eraltan, Ilhan; Arikan, Soykan; Ergen, H. Arzu; Küçücük, Seden; Isbir, Turgay (Archives of Medical Science, 2010)
Introduction : TNF-related apoptosis-inducing ligand (TRAIL) is a death ligand and also a member of the TNF superfamily. We aimed to investigate the possible relationship between TRAIL and breast cancer. Here, we report the results of the first association study on genetic variation in the TRAIL gene and its effect on breast cancer susceptibility and prognosis. Material and methods : A C/T polymorphism at 1595 position in exon 5 of the TRAIL gene was genotyped in a Turkish breast cancer case-control population including 53 cases (mean age: 55.09 ±11.63 years) and 57 controls (mean age: 57.17 ±17.48 years) using polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) analysis. Results : There were no differences in the distribution of TRAIL genotypes and frequencies of the alleles in the breast cancer patients and controls. A heterozygous TRAIL CT polymorphism in exon 5 was present in 8.3% of tumour stage III-IV and 48.8% of stage I-II patients, and in 42.1% of controls. The reduced frequency of this genotype in patients who had advanced tumour stage was statistically significant (p = 0.017). Conclusions : Our findings indicate that genetic variants of TRAIL at position 1595 in exon 5 might be associated with progression of breast cancer.